Strategi Pengembangan Desa Melalui Pemanfaatan Dana Desa di Desa Sako Margasari - Abdul Halim; Adianto Adianto (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: This study aims to determine the village development strategy through the use of village funds in the village of Sako Margasari, Kuantan Singing Regency, and the inhibiting factors of the village development strategy in the village of Sako Margasari, Kuantan Singingi Regency.Research Methodology: This research used a qualitative method with a descriptive approach.Results: The results of this study are that the village government in designing and implementing village development strategies still has obstacles that are experienced by the village government so that the development strategy is not optimal.Limitations: This study discusses the development strategy where this research looks at all environmental sectors through village funds as the basis for carrying out village development. Contribution: This research is expected to be useful and contribute as input and correction for the Head of Sako Margasari Village, Kuantan Singingi Regency. It is also useful for adding references to the literature at the Faculty of Social and Political Sciences, especially the Public Administration Study Program, as well as being a reference for subsequent writers with a focus on the study of Village Development Strategies Through Utilization of Village Funds in Sako Margasari Village, Kuantan Singingi Regency.